Cloning and Characterization of the Apoptotic Suppressor Gene P49 from Spodoptera Litura Nucleopolyhedrovirus - Mat Amin, Noriha (2005)
Baculoviruses possess two types of genes that can suppress apoptosis (programmed cell death), p35 and inhibitor of apoptosis (iap). The p49 gene of a Malaysian isolate of Spodoptera Iitura nucleopolyhedrovirus (SpltMNPV), a homolougue of baculovirus p35 gene was cloned and characterized. The open Reading Frame (OW) of SpltMNPV p49 gene was 13 17 bp long and encodes approximately 349 amino acid residues with a predicted molecular weight of 5 1.1 1 kDa. The SpltMNPV p49 gene shared 99% and 87% identity of nucleotide and amino acid sequence respectively to the SpltMNPV (AF325155), SpltMNPV (AF207549) and Spodoptera littoralis nucleopolyhedrovirus (SlNPV) p49 (AJ00675 1) obtained in the GenBank. The SpltMNPV P49 protein showed amino acid identities fiom 25 to 30% with 37 to 47% similarities to the p35 protein of Leucania separata, Spodoptera litura, Rachiplusia ou, Autographa californica and Bombyx mori nucleopolyhedroviruses, respectively. The SpltMNPV P49 protein molecule displays a potential caspase recognition site TVTDG at amino acid positions 94 to 98 in the polypeptide chain. The predicted secondary structure of SpltMNPV P49 protein including the hydrophilic (polar) and hydrophobic (basic) region was found to be similar to other P49 and P35 protein.